Envisioning Sustainable Futures of Localism: The Environmental Imagination of Local Currency Activists in Monnaie Léman and the Brixton Pound - Rycombel, Marlena (Zeitschrift für Theoretische Soziologie, 2026)
This article explores how local currency activists in Monnaie Léman and the Brixton Pound envision sustainable futures centered on localism. Based on 19 interviews and ethnographic fieldwork in Brixton and Geneva, it examines local currencies as payments limited to specific areas. In the short term, activists promote ethical consumption, short supply chains, environmental awareness, economic education, and strong local communities. Long-term visions focus on localized economies characterized by limited international trade, predominance of small businesses, and green, compact, community-oriented small towns with well-developed pedestrian and cycling infrastructure. Food is sourced from community gardens and nearby villages. These views stem from eco-habitus – mindset and practices of environmentally aware individuals with high cultural capital. Consumption through local currencies reflects the hipster economy, a term by Alessandro Gerosa describing consumption driven by nostalgia for local, family-like businesses. Since participation in local currency systems is linked to ethical consumption, this ecological strategy will be interpreted through Ulrich Beck’s concept of subpolitics and Zygmunt Bauman’s notion of individual utopias.